Bilateral uveal effusions in a 23-year-old man - Jeng-Miller, Karen W.; Gaier, Eric D.; Turalba, Angela V. (Digital Journal of Ophthalmology, 2018)
A 23-year-old white man with a past medical history of seasonal allergies and no prior ocular history presented emergently to the Massachusetts Eye and Ear Emergency Ward with acute, bilateral blurry vision of one day’s duration that had worsened overnight. He reported epiphora in both eyes and head pressure without headache. He described intermittent scintillations in both eyes of white and blue color. The patient reported taking a single dose of a “muscle relaxer” 10 days prior; he was unsure of the name of the drug. He denied any other new medications. He also reported an isolated episode of diarrhea on the day his blurry vision started. He denied eye pain, floaters, trauma, diplopia, fevers, rashes, recent travel, insect bites, myalgias, joint pain, dysuria, hematuria, melena, hematochezia, or shortness of breath. He cited occasional marijuana usage but no other recreational drug use.